Model Investasi Cryptocurrency dalam Upaya Pencegahan Tindak Pidana Pencucian Uang - Azzahra Natazia Ristina Goce (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to analyze cryptocurrency investment models in relation to the prevention of money laundering (Anti-Money Laundering/AML) activities. Cryptocurrency, as a growing form of digital investment, has garnered attention from regulators due to its potential money laundering risks. This paper explores preventive strategies that can be implemented within cryptocurrency investment systems, including the use of blockchain technology, KYC (Know Your Customer) procedures, and international regulations such as the Financial Action Task Force (FATF) guidelines. Through a qualitative method based on literature review and policy analysis, the study identifies investment models that can minimize money laundering risks while maintaining profitability for investors. These findings provide insights into the challenges and solutions in developing a safer cryptocurrency investment system that complies with AML regulations.